Prevalence of a gluten free diet and improvement of clinical symptoms in patients with inflammatory bowel diseases - Herfarth, Hans H. (Inflamm Bowel Dis, 2014)
BACKGROUND: Maintaining a gluten free diet (GFD) without an underlying diagnosis of celiac disease has enjoyed widespread acceptance in the USA. METHODS: We performed a cross-sectional study utilizing a GFD questionnaire in 1647 patients with inflammatory bowel diseases (IBD) participating in the CCFA Partners longitudinal, Internet-based cohort. RESULTS: A diagnosis of celiac disease (CD) and non-celiac gluten sensitivity (NCGS) were reported by 10 (0.6%) and 81 (4.9%) respondents, respectively. Three hundred fourteen (19.1%) participants reported having previously tried a GFD and 135 (8.2%) reported current use of GFD. Overall 65.6% of all patients, who attempted a GFD described an improvement of their GI-symptoms and 38.3% reported fewer or less severe IBD flares. In patients currently attempting a GFD, excellent adherence was associated with significant improvement of fatigue (p<0.03). CONCLUSION: In this large group of patients with IBD, a substantial number had attempted a GFD, of whom the majority had some form of improvement in GI-symptoms. Testing a GFD in clinical practice in patients with significant intestinal symptoms, which are not solely explained by the degree of intestinal inflammation, has the potential to be a safe and highly efficient therapeutic approach. Further prospective studies into mechanisms of gluten sensitivity in IBD are warranted.